MR-guided percutaneous interventional surgery robot system: A review - Weixi Zhang; Jiaxing Yu; Xikun Lu; Yanjie Xu (International Journal of Advanced Robotic Systems)
Background The combination of MR and robotic technology can improve surgical accuracy, shorten surgical time, and even improve the location of lesions that cannot be reached by traditional percutaneous intervention. However, owing to the limitations of the MR technology, MR-guided interventional robots face many difficulties and challenges in sensor, material selection, driving mode, and mechanical structure design. Aims The purpose of this paper is to summarize and analyze the previous MR-guided interventional robots, provide reference for future research on MR-guided interventional robots, and propose a concept suitable for MR-guided bionic breast interventional robots. Methods Starting from the field of MR-guided interventional robots, a systematic classification of MR-guided interventional robots for different body parts was conducted by reviewing the literature of the past 20 years. The structural design, surgical environment requirements, and experimental results of these robots are analyzed in detail. The advantages and disadvantages of each type of robot are summarized, providing a comprehensive overview of the current state of the field. Conclusion MR-guided interventional robots have demonstrated significant efficacy in percutaneous procedures. When designing MR-guided interventional robots, it is crucial to consider structural compactness, the selection of the drive system, and the compatibility of sensor modules. Based on an extensive review of relevant literature, this paper ultimately proposes a structural design concept of MR-breast interventional robot, which imitates the bloodsucking process of leeches.